Productivity of jambu (Acmella oleracea) using different soil water tensions and nitrogen rates under greenhouse condition - de Aviz, William Lee Carrera; de Lima, Joaquim Alves; da Silva, André Luiz Pereira [UNESP]; Gomes, Rafaelle Fazzi; Souza, Rodrigo Otávio Rodrigues de Melo; Santos, Helane Cristina Aguiar; de Oliveira, Pedro Daniel (Southern Cross Publishing, 2019)
Acmella oleracea (L.) R.K. is a native Amazon vegetable, known as jambu, which is widely used in regional cuisine and has aroused the interest of the pharmaceutical and cosmetic market. Thereby, this work aimed to study the effect of different soil water tensions and nitrogen rates on Jambu cultivation in the State of Pará. The experiment was conducted in a greenhouse for 30 days in 2016 testing Jamburana cultivar in a 10 × 10 cm spacing in the experiment. The experimental design was based on randomized blocks in a 4 × 4 factorial scheme with three replications. The treatments consisted of four soil water tensions (12, 18, 24 and 30 kPa) adjusted using drip irrigation, and four doses (0, 50, 100 and 150 kg ha -1 ) of nitrogen. The analyzed variables were fresh mass, plant height, productivity and water use efficiency. There was no interaction between soil water tensions factors and nitrogen rates for all variables. The results showed that the best water tension in the soil and nitrogen dose that provided better development and productivity of jambu were 18 kPa and 79 kg ha -1 , respectively.
Keywords: Acmella oleracea (L.) R.K.; Dripping; Nitrogen fertilization; Protected cultivation; Tensiometry